PSYCHOLOGICAL FACTORS FOR SUCCESSFUL EVALUATION OF SCIENTIFIC INFORMATION (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the role of cognitive processes in the process of assimilation of educational information, psychological factors for the successful assimilation of scientific information, the importance of mental processes formed in students, the inclusion of mental processes in accordance with the indicated stages of information assimilation.